Allegroscorrevole in Carter's First String Quartet: Crawford and the Ultramodern Inheritance. (December 2014) - Rao, Nancy Yunhwa
Abstract : Carter's First String Quartet was widely regarded as a landmark in American music by his contemporaries. This article examines two narratives of commentaries surrounding this pivotal work and argues that we bring Carter's own famous narrative of its "culmination of ideas" to bear on its analysis of both the important traits of dissonant writing that are central to Carter's musical language at the time and its close connection to Ruth Crawford's String Quartet 1931 . A study of the composition sketches related to Allegro scorrevole of the First Quartet uncovers several significant sketches that shed light on Carter's evolution of his dissonant aesthetics in this crucial work, reveal its original formal design, and show Carter's integral connection to ultramodernists.